Advanced Molecular Techniques Provide New Rigorous Tools for Characterizing Organic Matter Quality in Complex Systems. Issue 6 (16th June 2018) - Wilson, Rachel M.; Tfaily, Malak M.
Abstract: Carbon flux rates are widely understood to be substrate controlled; however, characterizing substrate quality continues to be a challenge. We suggest that, while optical measurements have their place, they are not the only, or the best, tool for characterizing organic matter quality . Nominal oxidation state of the carbon provides a thermodynamically relevant measure, which could be used as a metric of organic matter quality. Calculating nominal oxidation state of the carbon requires a suite of advanced complementary analysis but is then trivial to calculate from the resulting data sets. Key Points: While C emission rates are widely understood to be substrate controlled, characterizing organic matter quality remains a challenge Optical measurements are widely used, but they may not be the best tool for assessing organic matter quality NOSC provides a thermodynamically relevant measure, which could be used as a more rigorous metric of organic matter quality